Fluid modeling of exhaust gas dispersion for the University of Colorado School of Pharmacy: final report (July 1990-November 1990) - Parce, Douglas K., author; Meroney, Robert N., author; Fluid Mechanics and Wind Engineering Program, Department of Civil Engineering, Colorado State University?, publisher (Colorado State University. Libraries, 1991)
A wind-tunnel study was conducted in the Fluid Dynamics and Diffusion Laboratory at Colorado State University on a model of a planned addition to the University of Colorado Health Sciences Center (UCHSC). A 1:150 scale model of the new building, the School of Pharmacy (SOP) was added to an existing model of the UCHSC. It was used to collect information about the behavior of exhaust plumes and the probability of exhaust reentrainment into the new addition. Results are given in terms of normalized concentrations (K coefficients) to permit concentration estimates for alternative traffic, exhaust and wind speed combinations; but the decision as to the preferred configuration must be made with regard to current air-quality standards and building esthetics.
Prepared for Physical Plant and Maintenance Department, University of Colorado Health Sciences Center.
CSU contract (i.e. project) no. 2-98220.
CER90-91DKP-RNM-8.
Keywords: Automobiles -- Motors -- Exhaust gas; Air -- Pollution; Fluid dynamics